2004
DOI: 10.1074/jbc.m406917200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Nuclear Factor of Activated T Cells in Receptor Tyrosine Kinase and G Protein-coupled Receptor Agonist-induced Vascular Smooth Muscle Cell Motility

Abstract: In addition to their role in cytokine gene regulation in T cells, nuclear factors of activated T cells (NFATs) have been shown to be involved in cardiac development and hypertrophy. We have reported previously that NFATs play an important role in the regulation of vascular smooth muscle cell (VSMC) proliferation by receptor tyrosine kinase (RTK) and G protein-coupled receptor (GPCR) agonists, platelet-derived growth factor-BB (PDGF-BB) and thrombin, respectively. To understand the role of NFATs in vascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 39 publications
4
67
0
Order By: Relevance
“…It was reported that conditional expression of NFATc1 enhances pancreatic ␤-cell proliferation (37). In addition to these observations, work from our laboratory showed that NFATs mediate VSMC growth and migration in response to both RTK and GPCR agonists (17,18). A role for NFATs in the regulation of VSMC growth has also been supported by the findings that forced expression of constitutively active sarco/ endoplasmic reticulum calcium ATPase inhibits VSMC proliferation through inactivation of calcineurin and its target transcription factor NFAT (38).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was reported that conditional expression of NFATc1 enhances pancreatic ␤-cell proliferation (37). In addition to these observations, work from our laboratory showed that NFATs mediate VSMC growth and migration in response to both RTK and GPCR agonists (17,18). A role for NFATs in the regulation of VSMC growth has also been supported by the findings that forced expression of constitutively active sarco/ endoplasmic reticulum calcium ATPase inhibits VSMC proliferation through inactivation of calcineurin and its target transcription factor NFAT (38).…”
Section: Discussionsupporting
confidence: 64%
“…Previously, we have shown that NFATs play a role in the regulation of VSMC growth and migration (17,18). Towards understanding the mechanisms of NFATs in the regulation of VSMC migration, we have shown that these transcriptional factors mediate interleukin-6 expression as one of the effector molecules in receptor tyrosine kinase (RTK) and G protein-coupled receptor (GPCR) agonist-induced VSMC motility (18). In addition, we have reported the involvement of NFATs in injury-induced neointima formation (19).…”
mentioning
confidence: 99%
“…In RIE/GPRP-R cells, BBSmediated transcriptional induction of the Cox-2 gene is also calcium dependent, requiring activation of components of the AP-1 transcription factor complex, such as Fos/Jun proteins (Guo et al, 2001). Moreover, involvement of Gaq-coupled receptors as the GRP-R in the activation of NFAT and in the induction of NFATdependent genes has been described in a variety of cell types (Boss et al, 1996;Horsley and Pavlath, 2002;Liu et al, 2004). Noticeably, recent reports have proposed that NFAT proteins may play an important role in cancer, having shown a direct involvement of NFATmediated transcriptional regulation of different genes, including Cox-2 (Jauliac et al, 2002;Lara-Pezzi et al, 2002;Saurin et al, 2002;Neal and Clipstone, 2003;Holzmann et al, 2004;Yiu and Toker, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 IL-6 is produced from many cell types, including vascular smooth muscle cells (VSMCs). It was reported that the IL-6 expression in VSMCs is induced by IL-1, 11 platelet-derived growth factor 12 and Ang II. 13 The induction of IL-6 by Ang II is reported to be dependent on the activation of two transcription factors, cAMP-response element-binding (CREB) protein 13,14 and nuclear factor-kappa B (NF-kB).…”
Section: Introductionmentioning
confidence: 99%